2012
DOI: 10.1074/jbc.m111.275925
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factor NF-κB Regulates Expression of Pore-forming Ca2+ Channel Unit, Orai1, and Its Activator, STIM1, to Control Ca2+ Entry and Affect Cellular Functions

Abstract: Alterations of cytosolic Ca 2ϩ activity participate in the regulation of a wide variety of cellular functions including excitation-contraction coupling, exocytosis, migration, cell proliferation, and cell death (1-4). Cytosolic Ca 2ϩ is increased by release of Ca 2ϩ from intracellular stores and/or Ca 2ϩ entry across the cell membrane (5). Ca 2ϩ release from intracellular stores results in the stimulation of Ca 2ϩ release-activated Ca 2ϩ channel (CRAC) 2 (6, 7), which consists of the pore forming units Orai1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
62
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(69 citation statements)
references
References 67 publications
(56 reference statements)
7
62
0
Order By: Relevance
“…Because HNF4␣ expression is tissue specific (11,23,41), our results suggest that transcription factor-regulated STIM1 expression might be cell context dependent. Indeed, we failed to observe an NF-B effect on STIM1 expression in MCs (data not shown), as previously described in mast cell and pulmonary vascular endothelial cells (7,12). HNF4␣ is generally thought as a transcriptional activator and is known to activate a wide variety of genes involved in glucose, fatty acid, cholesterol, and amino acid metabolism (18,20,31,45).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Because HNF4␣ expression is tissue specific (11,23,41), our results suggest that transcription factor-regulated STIM1 expression might be cell context dependent. Indeed, we failed to observe an NF-B effect on STIM1 expression in MCs (data not shown), as previously described in mast cell and pulmonary vascular endothelial cells (7,12). HNF4␣ is generally thought as a transcriptional activator and is known to activate a wide variety of genes involved in glucose, fatty acid, cholesterol, and amino acid metabolism (18,20,31,45).…”
Section: Discussionsupporting
confidence: 79%
“…Little is known about the regulation of the abundance of STIM1, which could also affect channel function. In this regard, the transcription factor NF-B has been recently reported to promote STIM1 protein expression in mast cells and in vascular endothelial cells (7,12). In the present study, we showed that HNF4␣, a nuclear transcription factor, regulated STIM1 expression by functioning as a repressor in MCs.…”
Section: Discussionsupporting
confidence: 67%
“…It has been shown recently that the serum and glucocorticoid-inducible kinase SGK1 controls constitutive STIM1 transcription via NF-B signaling in bone marrow-derived mast cells (50). However, the transcriptional mechanism of STIM1 expression in response to inflammatory stimuli in ECs was not studied.…”
Section: Discussionmentioning
confidence: 99%
“…The process of F-actin disassembly was shown to be dependent on the increase of intracellular Ca 2ϩ (16,23). On the other hand, a powerful regulator of Ca 2ϩ entry and exocytosis in MCs is the serum-and glucocorticoidinducible kinase SGK1 (9,10,33). SGK1-deficient (sgk1 Ϫ/Ϫ ) MCs have a decreased FcεRI-dependent Ca 2ϩ entry and degranulation, and sgk1 Ϫ/Ϫ mice are thus protected against anaphylactic reaction, pointing to a strongly impaired MC function in vivo (33).…”
Section: Mcs and Sgk1mentioning
confidence: 99%
“…SGK1 is partially effective through phosphorylation of the ubiquitin ligase Nedd4-2 (neuronal precursor cells expressed developmentally downregulated), which ubiquitinates Orai1, thus preparing the channel protein for degradation (9). Moreover, SGK1 activates the transcription factor NF-B, which is required for Orai1 and STIM1 transcription (10). However, although regulation of Ca 2ϩ -dependent actin cytoskeleton dynamics is a crucial step for MC degranulation, nothing is known about the role of SGK1 in the process of actin restructuring.…”
Section: Mcs and Sgk1mentioning
confidence: 99%